New EM algorithms for source separation and deconvolution with a microphone array - Attias, H. (2003 IEEE International Conference on Acoustics, Speech, and Signal Processing, 2003. Proceedings. (ICASSP '03), 2003)
This paper presents new algorithms for source separation with a microphone array. Key to our algorithms are exploiting detailed source models, using subband filtering ideas to model the reverberant environment, and employing explicit models for background and sensor noise. We demonstrate strong performance which is robust to noise and reverberations. Good scaling properties are obtained using machine learning techniques.